ANALYSIS OF TENSILE STRENGTH OF HDPE 3D PRINTER FILAMENT PRODUCTION PROCESS THROUGH TEMPERATURE AND TIME VARIATIONS - Kharis, Abdul; Cristanto Putra Mbulu, Bernadus; Tugur Redationo, Nereus (Mechanical, Energy and Material (METAL), 2024)
Plastic waste is one of the problems currently being faced by countries in the world and Indonesia is one of them. Indonesia is the second world order of the world as a producer of plastic waste into the sea, which is 187.2 million tons after China which reaches 262.9 million tons. There are many kinds of plastic waste, including one of them HDPE plastic waste. In this study the researcher uses HDPE (High Density Poliyethylene) plastic waste which will be recycled into a filamentt of raw materials from 3D printers using temperature variations (200 ℃, 210 ℃, 220 ℃) with heating the heater band under 1 hour and above 1 hour and above 1 hour and above 1 hour and above 1 hour and above 1 hour and above 1 hour and above 1 hour and above obtained the highest capacity results at a temperature of 200 ̊C with heating time below 1 hour which produces filamentt production of 48.48 mm3/minute with a weight of 0.0028 kg/hour and motorcycle speed 10 rpm. Then 6 specimens from each variation will be photographed micro and tested to reach the point of breaking up. After that the calculation is done to get the maximum tensile voltage value and strain. Then obtained the highest maximum tensile voltage value with a temperature of 220 ̊C and heating plastic under 1 hour with a tensile strength value of 3,3344 N/mm2 This happens because the internal pore structure of the filament is formed more tightly and the plastic properties are still in good condition, this indicates that the load applied is evenly distributed on the filament